1953
DOI: 10.1002/aja.1000930205
|View full text |Cite
|
Sign up to set email alerts
|

Sequence of histological changes in the uterus and vagina of the rat during prologation of pseudopregnancy associated with the presence of deciduomata

Abstract: It has been reported by Olsen, Velardo, Hisaw, Dawson and Braverman ('51) that pseudopregnancy in rats can be prolonged beyond its usual duration by eliciting large decidual reactions, and that such prolongation is in general proportional to the amount of decidual tissue developed. These observations are contrary to those of Astwood and Greep ('38) who did not attempt to induce massive cleciduomata, but a r e in agreement with results of experiments by Ershoff and Deuel ( '43) and Peckham and Ureerie ( '48) in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
17
0

Year Published

1955
1955
1999
1999

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 69 publications
(18 citation statements)
references
References 13 publications
1
17
0
Order By: Relevance
“…106 This response elicits the formation of a deciduomata that is very similar (albeit not identical 107 ) to true decidua. Extensive observations based on this model have confirmed that the pseudo-decidual reaction is followed by the involution of the anti-mesometrial region 108 and preceded by the degradation of the luminal epithelium (in the rat, 109 in the mouse 110,111 ). Epithelial cells in the antimesometrial zone seem to detach progressively from the basal lamina and show clear signs of degradation (condensation and margination of the nuclear chromatin and dilation of the endoplasmic reticulum) which resemble those detected during normal implantation.…”
Section: Mechanisms Of Cell Death In the Uterusmentioning
confidence: 69%
“…106 This response elicits the formation of a deciduomata that is very similar (albeit not identical 107 ) to true decidua. Extensive observations based on this model have confirmed that the pseudo-decidual reaction is followed by the involution of the anti-mesometrial region 108 and preceded by the degradation of the luminal epithelium (in the rat, 109 in the mouse 110,111 ). Epithelial cells in the antimesometrial zone seem to detach progressively from the basal lamina and show clear signs of degradation (condensation and margination of the nuclear chromatin and dilation of the endoplasmic reticulum) which resemble those detected during normal implantation.…”
Section: Mechanisms Of Cell Death In the Uterusmentioning
confidence: 69%
“…Such orientation would appear to be essential for normal placental development and for the coordination of events that eventually free the embryo from the confines of the decidua and later from the uterus. Although chamber formation occurs to a limited extent in deciduoma [Krehbiel, 1937;Velardo et al, 1953;O'Shea et al, 19831, indicating that it is partly an intrinsic prop- erty of decidua formation and not just a result of the embryo occupying the space, the formation of a chamber in normal pregnancy probably requires an interaction between the stroma and the conceptus.…”
Section: U~s 11-16mentioning
confidence: 97%
“…They have been shown to contain glycogen (Bridgman, 1948), and their cytoplasmic granules are characterized by a diastase-fast periodic acid-Schiff reaction (Wislocki, Weiss, Burgos & Ellis, 1957) and a high content ofacid hydrolases (Bulmer, 1968). A variety of functions has been attributed to them, including the provision of nutrient to the developing embryo (Selye & McKeown, 1935), the liberation of a holocrine secretion facilitating disruption of the muscle coat during the expansion of the uterine wall (Bloch, 1964), and the production of relaxin (Velardo, Dawson, Olsen & Hisaw, 1953;Dallenbach-Hellweg, Battista & Dallenbach, 1965); none of these, however, has been proven or considered generally acceptable.…”
mentioning
confidence: 99%